1992
DOI: 10.1128/jvi.66.2.992-998.1992
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of virus spread and changes in levels of several cytokine mRNAs in the brain after intranasal infection of rats with Borna disease virus

Abstract: We have used the reverse transcriptase-polymerase chain reaction technique to gain insight into the pathogenesis of encephalitis caused by Borna disease virus (BDV). RNA specific for BDV was first detected in the olfactory bulb of intranasally infected rats at 6 days postinfection (p.i.). At 14 days p.i., high levels of BDV RNA were found in all brain regions, and at 26 days p.i., BDV-specific RNA was also present in the eye, nasal mucosa, and facial skin. In the chronic phase of the disease, BDV RNA was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 36 publications
1
62
0
Order By: Relevance
“…Several studies in rats have conclusively demonstrated a substantial brain uptake of radioactive labeled proteins, like horseradish peroxidase after application to the nasal or olfactory mucosa (Balin et al, 1986). Moreover, infections of brain tissue, like Borna disease (Shankar et al, 1992) and herpes simplex encephalitis (Eseri & Tomlinson, 1984;Stroop et al, 1984), may result from viruses entering the brain via the olfactory mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in rats have conclusively demonstrated a substantial brain uptake of radioactive labeled proteins, like horseradish peroxidase after application to the nasal or olfactory mucosa (Balin et al, 1986). Moreover, infections of brain tissue, like Borna disease (Shankar et al, 1992) and herpes simplex encephalitis (Eseri & Tomlinson, 1984;Stroop et al, 1984), may result from viruses entering the brain via the olfactory mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses have been widely used as transneuronal neuroanatomical tracers and interestingly for our present purpose many of them appear to infect the CNS via olfactory and/or trigeminal connections arising in the olfactory mucosa. Early investigations showed that a variety of viruses like Borna disease virus (Morales et al, 1988;Shankar et al, 1992), mouse hepatitis virus Barthold, 1988;Perlman et al, 1995), corona virus (Perlman et al, 1990) and mouse rabies virus (Lafay et al, 1991) enter the CNS along the olfactory pathways. Some recent additions are adenovirus type 1, flavivirus, lysosomal enzyme (Procario et al, 2012;Wolf et al, 2012;Yun et al, 2012), herpes simplex virus, entering also along the vomeronasal chemosensory system (Mori et al, 2005;Tomlinson and Esiri, 1983) and the human influenza virus (Majde et al, 2007).…”
Section: Intra-axonal and Transneuronal Transport Via Olfactory Pathwmentioning
confidence: 99%
“…After initial replication in the neurons located at the site of entry, BDV likely migrates intraaxonally in an anterograde or retrograde direction towards the CNS. The pathway of dissemination of BDV following intranasal inoculation of the rat has been thoroughly analyzed [140,190]. The virus initially replicates in the neuroreceptor cells of the olfactory epithelium.…”
Section: Neuroinvasion and Propagation Of Bdv In The Cnsmentioning
confidence: 99%
“…In the late stages of infection, BDV diffuses centrifugally, probably by using an anterograde axonal transport, and viral markers have been detected in peripheral nerves of all tissues and organs. Consequently, many tissues and organs become positive for viral markers [78,190,231]. These include lachrymal, salivary or sebaceous glands and, as a rule, any ectodermal/epithelial tissue that can be reached by BDV through central or peripheral innervation.…”
Section: Neuroinvasion and Propagation Of Bdv In The Cnsmentioning
confidence: 99%
See 1 more Smart Citation